Effects of chronic low dose organic arsenic exposure on the liver of Sprague Dawley rats - Shahida Saharuddin (Kulliyyah of Medicine, International Islamic University Malaysia, 2021)
Monosodium methylarsonate (MSMA) is a potent organoarsenical herbicide that is still being used in most Asian countries, despite its restriction in some other countries. Organic arsenic has been given less attention as it thought to be less toxic than inorganic counterpart. In most studies, the reported adverse effects were mainly on gastrointestinal system with little information on its severity to the liver. The objective of this study was to investigate the effect of organic arsenic (MSMA) exposure on the liver. Sixty rats were divided into three groups with different duration of exposure. The rats were given MSMA at 63.20 mg/kg daily for 2, 4 and 6 months through oral gavage. Serum samples were analysed for AST, ALT and ALP. Arsenic accumulation measurement, histomorphometric evaluation (H&E, PAS, reticulin and TUNEL staining) and ultrastructural study (scanning and transmission electron microscopy) were done on liver tissue. LSEC were isolated for gene expression study. Accumulation of arsenic were significantly higher in the MSMA-exposed rats compared to their control with the highest in the 6-month group [2-month (3.97± 2.28, p=0.009), 4-month (4.57±0.47), p<0.001 and 6-month (21.33±9.83, p=0.004) µg/g]. Both ALT [Control: 85.3± 13.0, Exposed: 52.0±5.2, p=0.005] and ALP [Control: 237.6±52.8, Exposed: 162.9± 28.9, p=0.007] were significantly lower in 4-month MSMA-exposed group than their control.The difference in AST level in all groups were not significant. Histopathological and ultra-structurally, focal necrotic, apoptotic and fibrotic changes in the liver with the reduction of organelles in hepatocytes were observed in 4- and 6-month exposed rats. In 4-month exposed group, the liver displayed increased in ballooning degeneration of the hepatocytes at zone 2, focal necrosis with minimal inflammatory infiltrates with fibrosis (mixture of stage 1 and 2). Disrupted hepatic cords with hepatocytes blebs were seen. In 6-month exposed rats, more extensive changes were noted. Cell cycle, apoptotic and DNA repair gene were affected in this exposure. At 2-month, cell cycle (Tp53), apoptotic (Tnfrsf1a) and DNA repair (Xrcc1) genes showed downward trend. However, at 4-month, both apoptotic-gene (Bax, Tnfsrf1a and Caspase 2) and the DNA repair gene (Xrcc1) expression showed upward trend. At chronic (6-month) exposure, only DNA repair gene (Mpg) showed upward trend. In conclusion, chronic MSMA exposure could be associated with potential liver injury. Thus, long term exposure to MSMA-contaminated water source should be taken seriously.